644 Severe Central Nervous System Dysfunction after Influenza Virus Infection in Paediatric Patients. (October 2012) - Genovese, O; Pulitanò, S; Crocco, S; Mancino, A; Tosi, F; Piastra, M
Abstract : Influenza virus can cause common respiratory tract infections and rarely multiorgan system disorders, resulting in mild infection, severe respiratory disease or systemic disease and complications. CNS dysfunction, an important complication of influenza infection includes IAE, a rapid progressive encephalopathy that usually presents in the early phase of influenza infection. Because of lack of inflammation in the CNS, IAE is always named influenza-associated acute encephalopathy, which includes acute necrotizing encephalopathy (ANE), presenting with fulminant encephalopathy and characteristic brain lesions following viral infection, which pathogenesis is not fully understood, but associated with unfavourable outcome. We present four new cases of central nervous system dysfunction subsequent to infection with Influenza Virus. All four cases had convincing evidence of preceding Influenza disease with no evidence of viable Influenza Virus in the cerebrospinal fluid. We propose that these cases represent examples of post Influenza central nervous system dysfunction. We also present a review of the literature regarding Influenza neurologic dysfunction and speculate on the underlying pathologic mechanisms.